Membrane-dependent dynamics and dual translocation mechanisms of ABCB4: Insights from molecular dynamics simulations - Veronica Crespi; Ágota Tóth; Angelika Janaszkiewicz; Thomas Falguières; Florent Di Meo (Computational and Structural Biotechnology Journal)
ABCB4 is an ATP-binding cassette transporter expressed at the canalicular membrane of hepatocytes and responsible for translocating phosphatidylcholine into bile. Despite the recent cryo-EM structures of ABCB4, knowledge about the molecular mechanism of phosphatidylcholine transport remains fragmented. In this study, we used all-atom molecular dynamics simulations to investigate ABCB4 dynamics during its transport cycle, leveraging both symmetric and asymmetric membrane models. Our results demonstrate that membrane composition influences the local conformational dynamics of ABCB4, revealing distinct lipid-binding patterns across different conformers, particularly for cholesterol. We explored the two potential mechanisms for phosphatidylcholine translocation: the canonical ATP-driven alternating access model and the “credit-card swipe” model. Critical residues were identified for phosphatidylcholine binding and transport pathway modulation, supporting the canonical mechanism while also indicating a possible additional pathway. The conformer-specific roles of kinking in transmembrane helices (TMH4 and TMH10) were highlighted as key events in substrate translocation. Overall, ABCB4 may utilize a cooperative transport mechanism, integrating elements of both models to facilitate efficient phosphatidylcholine motion across the membrane. This study provides new insights into the relationship between membrane environment and ABCB4 function, contributing to our understanding of its role in bile physiology and susceptibility to genetic and xenobiotic influences.